Genetic Prognostic Markers in Neuroblastoma - Zhu, PhD, MD, Haitao; Xiao, MD, Xianmin; Zheng, MD, Shan; Shen, PhD, Yiping; Wu, PhD, Bai-Lin (North American Journal of Medicine and Science, 2010)
Neuroblastoma is the most frequent pediatric extracranial tumor. It arises from embryonic neural crest cells and exhibits significant heterogeneity of clinical presentation and biologic behavior. Despite the application of aggressive treatments and multiple risk stratifications, prognosis of advanced stage of neuroblastoma still remains poor. So it is still a challenge in its prognostic evaluation to both clinicians and basic scientists and it is necessary to explore more molecular factors that correlate with outcome of this disease and develop a statistical predictor of survival for neuroblastoma patients. In this review, we summarize recent findings of chromosome alteration, gene expression, microRNA profiles and gene methylation status in neuroblastoma as well as their implications for predictors of neuroblastoma prognosis.